The Effect of Snake and Ladder Board Game on Students’ Grammar Achievement; A Case of SMPN 11 Kendari - Nisa, Nisa; Nurnia, Nurnia (Universitas Halu Oleo, 2021)
The objective of this research was to find out the effect of using snake and ladder board game on students’ grammar achievement at the eighth grade of SMPN 11 Kendari. The researcher used post-test only control group design. The population of this research was the eighth grade students at SMPN 11 Kendari.While, the samples of this research were class V.III.2 as the experimental group and class V. III.3 as control group. The technique of taking sample of this research used purposive sampling.The data were analized by using descriptive and inferential statistic. The hypothesis testing, the researcher applied an Independent samples ttest which calculated by using SPSS 16.0. The result found that students’ mean score in experimental group were 74.28, while mean scores of students in control group were 60.81 and the probability value 0.000 was lower than alpha 0.05 (0.000 < 0.05). Besides, ttest 8.564 was higher than ttable 2.000 (8.564 > 2.000). It shown that the alternative hypothesis was accepted and the null hypothesis was rejected. The large of effect size of snake and ladder board game was 0.99, it was categorized on moderate effect. Therefore, Snake and Ladder board game had a moderate significant effect on students’ grammar achievement at the eighth grade students at SMPN 11 Kendari.